Arachidonic acid attenuates brain damage in a rat model of ischemia/reperfusion by inhibiting inflammatory response and oxidative stress. (February 2018) - Qu, Y; Zhang, H-L; Zhang, X-P; Jiang, H-L
The aim of the present study was to study the effects of arachidonic acid (ARA) in a rat brain ischemia/reperfusion model induced by middle cerebral artery occlusion (MCAO). A total of 50 rats were randomly divided into five groups: control group, MCAO group, MCAO + ARA 0.3 g/kg group, MCAO + ARA 1 g/kg group, and MCAO + ARA 3 g/kg group. The MCAO + ARA groups received ARA by intraperitoneal injection daily for 14 consecutive days, while the rats in the control and MCAO groups were given equivalent volume of saline. We detected the Morris water maze test and pathological changes to investigate the ischemia/reperfusion injury. The protein levels of tumor necrosis factor-alpha and interleukin-6 in the hippocampus were detected by enzyme-linked immunosorbent assay kits. In addition, the activities of superoxide dismutase, glutathione peroxidase, and malondialdehyde were assayed in hippocampus homogenates to evaluate the oxidative stress after ischemia/reperfusion. The results indicated that ARA administration decreased biochemical parameters of inflammation and oxidative stress. Morris water maze test and histopathological examination further verified the protective effects of ARA on ischemia/reperfusion injury rats. These findings demonstrated that ARA could protect MCAO-induced brain injury rats by inhibition of inflammation and oxidative stress, suggesting that it may have potential as a therapy for cerebral ischemia/reperfusion injury.